Molecular Biology, Epidemiology, and the Elusive Nature of Pancreatitis. Issue 3 (March 2015) - Tenner, Scott
Abstract : N/A: The myriad of presentations of pancreatitis can cause confusion and controversy among clinicians affecting the diagnosis, treatment, and research of patients with these disorders. Although the disease is best thought of as a spectrum with classic presentations, the underlying pathophysiologic reasons for the differences in manifestations remains unknown. In this issue of the Journal, LaRusch and colleagues provide an elegant study combining epidemiology and molecular biology to explain why some patients with pancreatitis develop fibrosis chronic pancreatitis. The implications of the findings add to the growing request to support large multidisciplinary, combined genetic, and epidemiologic studies in pancreatic disease.